Effects of flow loop compressible volume position on system instabilities during flow boiling in micro-channel heat sinks - Lee, Jeongmin; Devahdhanush, V.S.; Darges, Steven J.; Mudawar, Issam (International journal of heat and mass transfer, 2022)
•This study investigates effects of location of flow loop compressible volume on instabilities in micro-channel systems.•Both high-frequency temporal parameter data and high-speed video records are analyzed.•Conditions leading to severe pressure drop oscillation (PDO) and relatively mild parallel channel instability (PCI) are identified.•Practical recommendations are provided regarding mitigation of instabilities in microchannel cooling systems. Much of published literature addressing flow instabilities in thermal management systems employing micro-channel modules has focused on the instability characteristics of the module alone, and far fewer studies have aimed at understanding the relationship between these characteristics and the compressible volume in the flow loop external to the module. From a practical point of view, developers of micro-channel thermal management systems for many modern applications are in pursuit of practical remedies that would greatly mitigate instabilities and their impact on cooling performance. The present study experimentally examines the effects of compressible volume location in a closed pump-driven flow loop designed to deliver FC-72 to a micro-channel test module having 38 channels with 315-µm hydraulic diameter. Three accumulator locations are investigated: upstream of the test module, downstream of the test module, and between the condenser and the pump. Both high-frequency temporal parameter data and high-speed video records are analyzed for ranges of mass velocity and heat flux, with inlet subcooling held constant at ∼14.5 °C. Pressure Drop Oscillation (PDO) is shown to dominate when the accumulator is situated upstream, whereas Parallel Channel Instability (PCI) is dominant for the other two locations. PDO shows severe pressure oscillations across the micro-channel heat sink, with rapid bubble growth and confinement, elongated bubble expansion in both directions, flow stagnation, and flow reversal (including vapor backflow to the inlet plenum) constituting the principal sequence of events characterizing the instability. Spectral analysis of pressure signals is performed using Fast Fourier Transform, which shows PDO extending the inlet pressure fluctuations with the same dominant frequency to other upstream flow loop components, with higher amplitudes closer to the pump exit. From a practical system operation point of view, throttling the flow upstream of the heat sink effectively eliminates PDO but renders PCI dominant, and placing the accumulator in the liquid flow segment of the loop between the condenser and the pump ensures the most stable operation.